Improving Students' Speaking Performance Through Team-Made Question Technique - Amin, Fatimah Hidayahni (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2022)
The major problems of this study were how to improve the speaking performance in terms of speaking accuracy covering acceptable pronunciation, correct grammar, and appropriate word choice and speaking fluency of the Business English students, Faculty of Languages and Arts, State University of Makassar, in 2005/2006 academic year, class B through the use of team-made question technique and what were the students’ attitudes toward the technique. In fact, based on the result of research, it is found that the use of team-made question technique can improve the students’ speaking performance in terms of speaking accuracy covering acceptable pronunciation, correct grammar, and appropriate word choice and speaking fluency and the students’ attitudes were strongly positive toward the technique. It is worth noting that the use of team-made question technique can create active and interactive learning situations concerning the effective implementation in teaching and learning process, especially in speaking class.Keywords: Speaking performance: accuracy and fluency, team-made question technique